Konflik Agraria Masyarakat Desa Tanjung Labu dengan CV SR Bintang Babel - Tsanayya Violeta Maharani (Departemen Ilmu Pemerintahan Fisip Unhas, 2021)
One of the agrarian conflicts in Indonesia is in Tanjung Labu Village, Lepar Pongok District. The conflict was caused by the presence of land mining carried out by CV SR Bintang Babel in Tanjung Labu Village which was categorized as a small island. As a result of mining activities without the socialization of the SR. SR. Bintang Babel, people feel discriminated against and cause repressive actions on SR. Bintang Babel CV. The purpose of this study is to map mining conflicts in the village of Tanjung Labu. This mining conflict involves CV SR Bintang, the community, the government and Walhi. This research method uses descriptive qualitative method by conducting in-depth interviews and documentation studies. The results of this study indicate that CV SR. Bintang Babel exploits tin on land and this creates a conflict between CV SR. Bintang Babel with the people of Tanjung Labu Village. Land conflicts, conflict mapping, small islands.